1978
DOI: 10.1177/014662167800200410
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validation of the Inventory of Learning Processes

Abstract: Two correlational investigations are described which are aimed at establishing the construct validity of the dimensions assessed by the scales of the Inventory of Learning Processes. The Synthesis- Analysis scale is assumed to assess "deep" (e.g., semantic) information-processing habits. It was positively related to critical thinking ability, curiosity, and both independent and conforming achievement-striving behaviors but negatively related to anxiety. The Study Methods scale is assumed to assess the habits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
4

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 19 publications
2
24
0
4
Order By: Relevance
“…Craik states that &dquo;preliminary or shallow analyses are concerned with physical aspects of the stimulus, whereas subsequent, deeper analyses are concerned more with meanings and associative relationships&dquo; (1977, p. 680). Research employing the ILP has shown that scores on the Synthesis-Analysis scale are related positively to prose and verbal learning, note-taking efficiency, critical thinking ability, and achievement motivation, while relating negatively to anxiety (Ribich, 1976;Schmeck & Ribich, 1978;Schmeck et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Craik states that &dquo;preliminary or shallow analyses are concerned with physical aspects of the stimulus, whereas subsequent, deeper analyses are concerned more with meanings and associative relationships&dquo; (1977, p. 680). Research employing the ILP has shown that scores on the Synthesis-Analysis scale are related positively to prose and verbal learning, note-taking efficiency, critical thinking ability, and achievement motivation, while relating negatively to anxiety (Ribich, 1976;Schmeck & Ribich, 1978;Schmeck et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The internal consistency of deep processing has been measured at α = .84, and at α = .86 for elaborative processing (Schmeck et al, 1991). Studies have found good evidence for construct validity and structural validity of the ILP-R based on factor analysis (Schmeck & Ribich, 1978;Schmeck et al, 1977), as well as cross-validation with international samples (Kozminsky, 1988).…”
Section: Downloaded By [Stony Brook University] At 08:33 01 November mentioning
confidence: 99%
“…Study methods (Biggs 1970;Goldston et aI. 1977;Holtzman, Brown, and Farquhar 1954;Houston 1987;Ramanaiah, Ribich, and Schmeck, 1975;Schmeck and Ribich 1978;Schmeck, Ribich, and Ramanaiah 1977;Thompson 1976) 4 known reliability and validity were used for the remaining variables, when available. New scales were constructed and existing scales adapted when necessary, so that the scales were balanced in keying and the items were minimally redundant in content and suitable for incoming college students in this country.…”
Section: Identifying Variablesmentioning
confidence: 99%